Implementasi Pendidikan Aqidah Akhlak dalam Pembentukan Karakter Religius pada Siswa Kelas III MI Muhammadiyah Desa Simpang Kubu - Ardiansyah; Wismanto; Sakban (Yayasan Cendekia Gagayunan Indonesia, 2024)
The aim of this research is to determine the role of the Akhlak faith teacher in shaping the religious character of class III students at MI Muhammadiyah Simpang Kubu Village. This research method uses a qualitative research type. Qualitative research is an inquiry strategy that emphasizes the search for meaning, concepts, characteristics, symptoms, symbols and descriptions of a phenomenon, focused and multimode, natural and holistic in nature. Prioritizes quality, uses several methods, and is presented negatively. Data collection was carried out by means of observation, interviews and documentation. For the validity of the data, triangulation techniques are used, namely comparing all the different data obtained. The results of the research show that the role of moral aqidah teachers in shaping students' religious character, especially the values ​​of discipline and responsibility, has increased, although there are still some students who have not changed. The moral aqidah teacher's efforts in forming students' religious character have been maximal even though there are some students who still need to be further directed. The role of the moral aqidah teacher is very important in forming religious character in students.